Aplicación web para la evaluación de resultados de las actividades de servicio a la comunidad y prácticas preprofesionales en la carrera de Ingeniería en Informática y Sistemas Computacionales. - Cofre Anguisaca, Edison Gabriel (2020)
This project is aimed at developing a web application that allows evaluating the results of the activities of Liaison with the Society of the Career of Computer Science and Computer Systems. This application will allow to systematically execute processes, procedures and activities of service to the community and pre-professional practices.